إصلاح قطاع المالية العامة في العراق (دراسة إستشرافية) (المجلة العراقية للعلوم الاقتصادية, 2018)
The public finance reform in Iraq requires taking many procedures from Iraqi government. These procedures consist of two parts; one of them reforms the government expenditure and another reform the government revenue. The government has to reorganize its expenditures and reduce it as a percent of GDP, by allowing policy take care of the low income families. Meanwhile, the government has to reconstruction its revenue by searching for new methods to increase it especially in tax revenue side. This strategy would make the role of the government more efficient and definite and with obvious target in economy.